Influence of Light Intensity on Tobacco Responses to Drought Stress - Rasool, Brwa (Kurdistan Journal of Applied Research, 2021)
The influence of high irradiance, drought stress and their cross-talk were explored in tobacco plants (Nicotiana tobaccum) grown under low light (250 ?mol m-2 s-1) irradiance (LL) and high (1600 ?mol m-2 s-1) irradiance (HL) then exposed to water deficient condition for 7 or 14 days. The detached leaves of HL-treated plants showed less water loss compared to LL plants. The HL-treated and 7 days drought-stressed plants had higher fresh and dry weights, as well as water content than the LL and drought-stressed leaves. The survival rate in 21 days drought-stressed plants after 3 days of re-watering was 50% in HL-grown and 0% in LL-grown plants. A transcriptome profiling analysis of the tobacco responses to light intensity highlights the increased abundance of a large group of drought-related transcripts including DROUGHT-RESPONSIVE ELEMENT BINDING FACTORS (DREBs), C-REPEAT/DROUGHT-RESPONSIVE BINDING FACTOR 1 (CBF1), GLYCINE-RICH RNA BINDING PROTEINS (GRPs), WRKY33 and MYCs transcription factors, as well as zeaxanthin epoxidase, which play as a regulator of plant responses to water deficient condition. These findings identify light-dependent changes in the cell redox state that limit water loss and enhance plant responses to drought stress.